Navigating the Storm: Integrative Review of Attrition Factors Among Undergraduate Nursing Students - Carmela Theresa T. De Leon (Humanistic Network for Science and Technology (HNST), 2018)
Studies have been conducted worldwide on attrition, a persistent issue affecting nursing education. Most focus on predictive factors of attrition or at-risk populations. Few focus on those who experienced it and their actual reasons. This integrative review seeks to investigate published literature, both qualitative and quantitative researches about actual or perceived factors that lead to temporary or permanent attrition among undergraduate nursing students. The review includes eight articles published in major health literature databases from 1996 to 2016. The lack of a unified definition of attrition is a major limitation in various studies. Findings reveal that there is no single reason why a student decided to leave. The complex factors identified were thematically grouped in three systems utilizing the Micro-meso-macro System Framework of personal (micro-system), institutional (meso-system) and professional (macro-system) levels. Better conceptual and operational definition of attrition is needed to facilitate more accurate reporting in institutions of higher education. Stakeholders affected by nursing student attrition need to address each identified factor in the multiple and inter-related levels to determine a comprehensive and collaborative plan to address the growing issue of attrition in nursing education. Keywords: Nursing students, Attrition, Factors, Undergraduate